Ambiguity, Woman and Otherness in Ari Aster’s Midsommar - Moya Sánchez, Lucía (Journal of Artistic Creation and Literary Research, 2025)
If films are cultural texts, as such, they express values and fears of the time in which they are made. Midsommar, because of the ambiguity it sets out to convey and so commented on by critics and on social media, accounts for a series of anxieties present today: in essence, the ambiguous nature of good and evil, and how these manifest themselves in our society in a confusing way, stressed by new concepts that require deep reflection. Thus, this paper will argue that Midsommar speaks of good and evil, but also of the familiar and the foreign, the familiar and the strange, the individual and the communal. To be effective and provoke critical reflection, these dualities must be perceived by the audience. For this reason, I have included in this article a survey that was conducted to verify whether the film did indeed elicit the contradictory emotions that the director intended in the audience. I will therefore make some observations regarding the survey responses to reflect on the emotional journeys of Dani, the film’s protagonist, and the audience. Next, I will explore the reasons behind these emotional swings through feminist criticism and studies of otherness: it is through these emotions that viewers can notice the existence of an ambiguity between good and evil, between what is ours and what is foreign, between the individual and the communal. Finally, I will question whether ambiguity exists, and what type of ambiguity is specifically present in Midsommar.